Analysis of West Sulawesi Provincial Government Policy on the Management of the Bala - Balakang Island - Citra N. Fariaty; Aco Nata Saputra; Asriani (Kirana Publisher (KNPub), 2022)
This paper analyzes the implementation of the West Sulawesi provincial government policy towards the ownership status of the Bala-balakang island and also the impact of the West Sulawesi provincial policy on the ownership status of the Bala-balakang island. The Provincial Government of West Sulawesi has attempted several programs to defend the Bala-balakang Island from lawsuits from East Kalimantan. The Bala-balakang Archipelago has enormous potential for natural resources including the potential for marine tourism and fisheries. However, until now the West Sulawesi government is still having problems continuing to intervene because of the long distance to the island. Keywords: policy, conflict, ownership status of the territory